Pengaruh Mengintegrasikan Gadget dalam Praktik Parenting Modern Perspektif Al-Qur’an - Riska Nur Afriani; Sori Monang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Considering the development of very sophisticated technology, there are many tasks for parents in implementing parenting patterns for children. One of the problems in the current digital era is children's use of gadgets which affects their growth and development. Parents need to monitor and guide children in their use of digital devices to ensure that this does not interfere with their overall development. Children's problems are not new problems, but digital developments (information and communication technology) are believed to have a big influence on children's problems, including children's behavior. The digital era has an impact on easy access to information for children, including their curiosity about current technology. Children's problems are identified in a generation that is familiar with technological developments in the form of gadgets. The use of gadgets by children has positive and negative consequences. So this article aims to examine the positive and negative impacts of integrating gadgets in parenting, as well as solutions for parental supervision of children. The research uses the library research method, which is an approach to collecting data by reading books, magazines, journals, quoting the opinions of various tafsir scholars and other sources of information available in the library. Researchers used qualitative methods to collect existing data until finally it was discovered that integrating gadgets had a lot of influence on the continuity of parenting. In this case, the parenting process must also balance its practice with world and religious concepts. The Al-Qur'an itself provides many instructions regarding parenting patterns in the family. Therefore, integrating gadgets in parenting without being guided by the Koran will cause harm to parents. Islam illustrates that whether good or bad really depends on the parents' efforts in educating their children. Integrating gadgets in parenting practices can help parents provide modern education, but it also has bad effects if they are implemented incorrectly, therefore it requires effective supervision of children in today's digital era.